Evangelization or colonization? - Nascimento, Analzira (Global voices., 2021)
Many years of cross-cultural work in Angola have led Analzira Nascimento to deeply rethink mission, especially in countries marked by western colonialization. As you read, be sure to 'recognise' the Spirit who moves people to participate in God's mission in a world marred by suffering and injustice. Imagine Christian mission without the dichotomies of 'us' and 'them', mission which is relational and dialogical. These are some of the questions this book addresses which forces the reader to reimagine participation in God's mission as a meeting of strangers brought together by the work of the Holy Spirit.